Mechanosensitive ion channel Piezo1 modulates the response of rat hippocampus neural stem cells to rapid stretch injury - Emanuele Mocciaro; Madison Kidd; Kevin Johnson; Elizabeth Bishop; Kathia Johnson; Ya Ping Zeng; Cristiana Perrotta; Maria-Adelaide Micci (PLoS ONE, 2025)
Traumatic brain injury (TBI) is one of the primary causes of long-term brain disabilities among military personnel and civilians, regardless of gender. A plethora of secondary events are triggered by a primary brain insult, increasing the complexity of TBI. One of the most affected brain regions is the hippocampus, where neurogenesis occurs throughout life due to the presence of neural stem cells (NSC). Preclinical models have been extensively used to better understand TBI and develop effective treatments. Among these, rapid stretch injury has been used to mimic the effect of mechanical stress produced by a TBI on neurons and glia in vitro. In this study, we aimed to determine the impact of rapid stretch on the viability, proliferation, and differentiation of NSC isolated from rat hippocampus (Hipp-NSC) and to determine the role of the stretch-activated ion channel Piezo-1 in modulating their response to mechanical stress. We found that while rapid stretch (30 and 50 PSI) reduced Hipp-NSC viability (measured as a function of LDH release), it did not change their proliferation and differentiation potentials. Interestingly, rapid stretch in the presence of a selective Piezo-1 inhibitor, GsMTx4, or Piezo1 targeting siRNA, directed Hipp-NSC differentiation toward a neurogenic lineage. Additionally, we found that inhibiting Piezo1 with the addition of a rapid stretch injury increased the expression of miRNAs known to regulate neurogenesis. This work uses a novel approach for studying the effect of mechanical stress on NSC in vitro and points to the critical role the stretch-activated ion channel Piezo-1 has in modulating the impact of TBI on hippocampal neurogenesis.